THE PRIORITY OF MER-C IN GIVING SIGNIFICANCE HUMANITARIAN ASSISTANCE TO PALESTINIANS IN GAZA AFTER MAVI MARMARA ACCIDENT IN 2010 - Faris Sanjaya (2012)
This undergraduate thesis is written to discuss about the priority of MER-C in giving significance humanitarian assistance toward Palestinians in Gaza after Mavi Marma accident 2010. The question is what. Based on problem solving theory that used, Gaza people need a longterm assistance because the war conflict and humanity problems has been going for a long time. Than MER-C build a traumatology and rehabilitation hospital to help the victims of war in Gaza. Other that, this undergraduate thesis